Self-Reflection as a Mediator Between Solitude and Identity Development - Binti Zulkifli, Nur Aisyah; Maisarah, Syarifah (Journal of Assessment and Research in Applied Counseling (JARAC), 2024)
Objective: This study aimed to examine the mediating role of self-reflection in the relationship between solitude and identity development among Malaysian adolescents. Methods and Materials: A descriptive correlational design was employed with a sample of 476 adolescents selected based on the Morgan and Krejcie table using stratified random sampling from various educational institutions in Malaysia. Participants completed three standardized instruments: the Preference for Solitude Scale (PSS), the Self-Reflection and Insight Scale (SRIS), and the Ego Identity Process Questionnaire (EIPQ). Data were analyzed using SPSS-27 for descriptive and Pearson correlation analyses, and AMOS-21 was used for Structural Equation Modeling (SEM) to examine direct and indirect paths and assess model fit through standard indices. Findings: Descriptive results showed moderate to high levels of solitude (M = 35.42, SD = 5.76), self-reflection (M = 67.89, SD = 9.13), and identity development (M = 101.47, SD = 10.86). Pearson correlations revealed significant positive relationships among solitude, self-reflection, and identity development (p < .001). The SEM model indicated good fit (χ² = 142.36, df = 64, χ²/df = 2.22, GFI = 0.94, AGFI = 0.91, CFI = 0.96, TLI = 0.95, RMSEA = 0.051). Self-reflection significantly mediated the relationship between solitude and identity development. The indirect effect of solitude on identity development through self-reflection (β = 0.22, p < .001) complemented the direct effect (β = 0.22, p < .001), resulting in a total standardized effect of β = 0.44 (p < .001). Conclusion: The findings highlight the essential role of self-reflection in enhancing the developmental impact of solitude on identity formation. Encouraging reflective practices among adolescents can optimize the psychological benefits of solitude and support more coherent identity development during formative years.